PDL1 expression is associated with longer postoperative, survival in adrenocortical carcinoma. (2nd November 2019) - Billon, Emilien; Finetti, Pascal; Bertucci, Alexandre; Niccoli, Patricia; Birnbaum, Daniel; Mamessier, Emilie; Bertucci, François
ABSTRACT: Adrenocortical carcinomas (ACCs) are heterogeneous cancers associated with a very poor prognosis. The improvement of prognostic tools and systemic therapy are urgently needed. Targeting the immune system using checkpoint inhibitors such as PD1/PDL1 inhibitors is an attractive novel therapeutic strategy for poor-prognosis tumors. Multiple clinical trials are ongoing, including in advanced ACC. However, PDL1 expression has been studied in ACC in only one heterogeneous series of 28 clinical samples. Here, we have retrospectively analyzed PDL1 mRNA expression in 146 clinical ACC samples and searched for correlations between expression and biological and clinicopathological data, including post-operative disease-free survival (DFS). PDL1 mRNA expression was heterogeneous across samples. "PDL1-high" tumors were not associated with the classical prognostic variables but were associated with longer DFS in both uni- and multivariate analyses. High PDL1 mRNA expression was associated with biological signs of the cytotoxic local immune response. Supervised analysis between "PDL1-high" and "PDL1-low" tumors identified a robust 370-gene signature whose ontology analysis suggested the existence in "PDL1-high" tumors of a cytotoxic T-cell response, however, associated with some degree of T-cell exhaustion. In conclusion, PDL1 mRNA expression refines the prognostication in ACC and high expression is associated with longer DFS. Clinical validation at the protein level and functional validation are required to fully understand the role of PDL1 in ACC. Reactivation of dormant tumor-infiltrating lymphocytes by PDL1-inhibitors could represent a promising strategy in "PDL1-high" ACCs, supporting the ongoing clinical trials.